Physical activity prevents tumor metastasis through modulation of immune function - Zheng, Aiping; Zhang, Lei; Yang, Jiaqing; Yin, Xiaomeng; Zhang, Tao; Wu, Xin; Ma, Xuelei (Frontiers in Pharmacology, 2022)
Metastasis is responsible for 90% of deaths in cancer patients. Most patients diagnosed with metastatic cancer will die within 5 years. Physical exercise is good for health and has become an emerging adjuvant therapy for cancer survivors. Regular moderate exercise substantially lowers the risk of several cancers, alleviates cancer-related adverse events, enhances the efficacy of anti-cancer treatments, and improves the quality of life of cancer patients. However, the mechanism by which physical exercise regulates tumor metastasis remains poorly understood. Recently, some studies suggested that the modulation of the immune system through physical exercise can significantly affect the exercise-dependent prevention of tumor metastasis. Revealing the mechanisms of physical exercise inhibiting tumor metastasis could upgrade our understanding of cancer biology and help researchers explore new therapeutic strategies to improve survival in cancer patients. The purpose of this review is to discuss and summarize the critical link between immune function and exercise in metastasis prevention.